2015
DOI: 10.1111/bju.13212
|View full text |Cite
|
Sign up to set email alerts
|

Oncological control associated with surgical resection of isolated retroperitoneal lymph node recurrence of renal cell carcinoma

Abstract: ObjectiveTo evaluate the outcome of patients after surgical resection of isolated retroperitoneal lymph node (RPLN) recurrence of renal cell carcinoma (RCC) using a multicentre international cohort. Patients and MethodsIn all, 50 patients were identified who underwent resection of isolated RPLN recurrence of RCC at four institutions after nephrectomy for pT any N any M0 disease. Progression-free (PFS) and cancer-specific survival (CSS) were estimated using the Kaplan-Meier method. Cox proportional hazards regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…). The number of studies included for each specific aim are as follows: PA1/PA2: nine reports representing eight unique studies []; SA1: six studies (of which two represented separate analyses of the same dataset) ; SA2: 15 studies (of which one single‐institutional study was included in a multi‐institutional study) ; SA3: five studies ; SA4: 10 studies ; and SA5: 18 studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). The number of studies included for each specific aim are as follows: PA1/PA2: nine reports representing eight unique studies []; SA1: six studies (of which two represented separate analyses of the same dataset) ; SA2: 15 studies (of which one single‐institutional study was included in a multi‐institutional study) ; SA3: five studies ; SA4: 10 studies ; and SA5: 18 studies .…”
Section: Resultsmentioning
confidence: 99%
“… ACM, all‐cause mortality; CSM, cancer‐specific mortality; CSS, cancer‐specific survival; ECOG PS, Eastern Cooperative Oncology Group Performance Status; HR, hazard ratio; LN, lymph node; LND, lymph node dissection; MFS, metastasis‐free survival; MVA, multivariable analysis; NR, not reported; OS, overall survival; PFS, progression‐free survival. *Single‐institutional study also included in multi‐institutional study by Russel (2016) . † Survival estimate for pN+ V0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Russell et al identi ed 50 patients who underwent resection of isolated retroperitoneal lymphadenectomy (RPLN) recurrence of RCC after nephrectomy. They found that those patients with a longer interval from nephrectomy to RPLN recurrence had signi cantly decreased risks of progression after resection, suggesting that this variable may be used in patient selection [16].…”
Section: Discussionmentioning
confidence: 99%